Achievement of European guideline-recommended lipid levels post-percutaneous coronary intervention: A population-level observational cohort study. (9th April 2020) - Harris, Daniel E; Lacey, Arron; Akbari, Ashley; Torabi, Fatemeh; Smith, Dave; Jenkins, Geraint; Obaid, Daniel; Chase, Alex; Gravenor, Mike; Halcox, Julian
Abstract: Aims: European Society of Cardiology/European Atherosclerosis Society 2019 guidelines recommend more aggressive lipid targets in high- and very high-risk patients and the addition of adjuvant treatments to statins in uncontrolled patients. We aimed to assess (a) achievement of prior and new European Society of Cardiology/European Atherosclerosis Society lipid targets and (b) lipid-lowering therapy prescribing in a nationwide cohort of very high-risk patients. Methods: We conducted a retrospective observational population study using linked health data in patients undergoing percutaneous coronary intervention (2012–2017). Follow-up was for one-year post-discharge. Results: Altogether, 10, 071 patients had a documented LDL-C level, of whom 48% had low-density lipoprotein cholesterol (LDL-C)<1.8 mmol/l (2016 target) and (23%) <1.4 mmol/l (2019 target). Five thousand three hundred and forty patients had non-high-density lipoprotein cholesterol (non-HDL-C) documented with 57% <2.6 mmol/l (2016) and 37% <2.2 mmol/l (2019). In patients with recurrent vascular events, fewer than 6% of the patients achieved the 2019 LDL-C target of <1.0 mmol/l. A total of 10, 592 patients had triglyceride (TG) levels documented, of whom 14% were ≥2.3 mmol/l and 41% ≥1.5 mmol/l (2019). High-intensity statins were prescribed in 56.4% of the cohort, only 3% were prescribed ezetimibe, fibrates or prescription-grade N-3 fatty acids. Prescribing of these agents was lower amongst patients above target LDL-C, non-HDL-C and triglyceride levels. Females were more likely to have LDL-C, non-HDL-C and triglyceride levels above target. Conclusion: There was a low rate of achievement of the new European Society of Cardiology/European Atherosclerosis Society lipid targets in this large post-percutaneous coronary intervention population and relatively low rates of intensive lipid-lowering therapy prescribing in those with uncontrolled lipids. There is considerable potential to optimise lipid-lowering therapy further through statin intensification and appropriate use of novel lipid-lowering therapy, especially in women.